The Association Between Peer Influence and Dating Behavior Among Adolescents at a High School in Rural Area: A Cross-Sectional Study - Amalia, Ananda Putri; Silvanasari, Irwina Angelia (Journal of Rural Community Nursing Practice, 2025)
Background: Dating behavior among adolescents today leads to risky dating behavior that has an impact on premarital sexual behavior. Teenagers are curious about new things and can be influenced by their partners, environment, and peers. Purpose: This study aims to analyze the relationship between the role of peers and dating behavior in adolescents. Methods: This research design is quantitative with a cross-sectional approach. The population at State Senior High School "X" Jember was 121 students, with a sample size of 93 students. The sampling technique used was simple random sampling. The independent variable is the role of peers, and the dependent variable is dating behavior. These two variables were measured using a questionnaire on the role of peers and dating behavior. Univariate analysis was performed with frequency distribution. Bivariate analysis using Fisher's Exact test. Results: The results showed that almost all peer roles were in the positive category, with a percentage of 84.9%. Most respondents showed non-risky dating behavior, 72.0%. Fisher's Exact test results show that the p-value (0.000) is smaller than α (0.05). This means the alternative hypothesis is accepted and indicates a relationship between peer roles and adolescent dating behavior. Conclusions: Positive peer roles tend to lead to non-risky dating behavior. Therefore, adolescents should be more careful in choosing peers to avoid engaging in risky dating behavior.